Public Participation in, and Awareness about, Medical Research Opportunities in the Era of Clinical and Translational Research. Issue 2 (14th January 2013) - Davis, Matthew M.; Clark, Sarah J.; Butchart, Amy T.; Singer, Dianne C.; Shanley, Thomas P.; Gipson, Debbie S.
Abstract Context In the United States, levels of public participation in medical research in the era of Clinical and Translational Science Awards (CTSAs) are unknown. Methods In 2011, a household survey was administered to a sample of U.S. adults, asking whether they (and children <18 years old) had participated, or were aware of opportunities to participate, in medical research. Respondents living within 100 miles of CTSA sites were identified. Regression analyses of participation and awareness (PA) were performed, applying sampling weights to permit nationally representative inferences. Results Overall, 2, 150 individuals responded (completion rate = 60%); 65% of adults and 63% of families with children resided within 100 miles of ≥1 CTSA location. Research participation rates were 11% among adults and 5% among children. Among nonparticipants, awareness rates were 64% among adults and 12% among parents of children. PA among adults was associated with higher income and education, older age, presence of chronic conditions, and living within 100 miles of four specific CTSA locations. For children, PA was associated with higher household income and parents' chronic health conditions. Conclusions PA of medical research opportunities is substantially higher for adults than children. Higher PA levels near specific CTSAs merit investigation to identify their successful approaches.